STRATEGI MAJALAH UNIVERSUM DALAM ERA REVOLUSI INDUSTRI 4.0 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses the Universum Magazine Strategy in the 4.0 Revolution Era. The research objectives to find out the strategy of the UIN Alauddin Makassar universal magazine in changing information flow and to find out the impact of information shifting on the image of UIN Alauddin Makassar on the community. The source of the data in this study was obtained from direct interviews with several informants in the research locations including, the Head of Public Relations Section of UIN Alauddin Makassar, Universum Magazine Journalist, and Universum Magazine Reader. Data processing and analysis techniques, namely through the process of data reduction, data presentation, drawing conclusions and verification. The results showed that the strategy of the universal magazine UIN Alauddin Makassar in changing the flow of information including developing universal magazines from the printed version to the digital version and the ability to adapt to changes must be clever in viewing audience behavior.